Philippe Lacoue-Labarthe: Representation and the Loss of the Subject - Martis, John (Perspectives in Continental Philosophy, 2005)
This is the first full-length book in English on the noted French philosopher Philippe Lacoue-Labarthe. Martis introduces the range of Lacoue-Labarthe's thinking, demonstrating the systematic nature of his philosophical project. Focusing in particular on the dynamic of the loss of the subject and its possible post-deconstructive recovery, he places Lacoue-Labarthe's achievements in the context of related philosophers, most importantly Nancy, Derrida, and Blanchot. John Martis, S.J. teaches at the United Faculty of Theology, Melbourne, Australia, as a member of Jesuit Theological College, where he is Professor of Philosophy and Academic Principal.